Towards a Policy for Bilingual education in Developing Countries - Stroud, Christopher (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
Language can make a difference to peoples' lives in many ways. On one dimension, language empowers by serving as a resource for individuals to constitute and trans-form social and personal identities and by providing access to important socio-economic and political markets. Language can empower because it does not merely reflect a pre-existing reality; it is itself - under certain conditions - an instrument in the constitution of these realities, by providing a new version of meaning that offers speakers a fresh interpretation or alternative perspective on reality. The multilingual proficiency that social elites have in important global languages such as English, French, German, and today, Chinese, is a case in point. These elites have long recognized that mastery of many languages is an economic asset to be cultivated and passed on to successive generations.